Ready for School: A Multi-Dimensional Approach to School Readiness Assessment in Hispanic Children from Puerto Rico - Mary Rodríguez-Rabassa; Kamalich Muniz-Rodriguez; Allison A. Appleton; Marilyn Borges-Rodríguez; Nicole E. Ruiz-Raíces; Francisco J. Reyes-Santiago; Odette Olivieri-Ramos; Luisa I. Alvarado-Domenech (Behavioral Sciences, 2025)
School readiness during early childhood is crucial for future academic success. Existing guidelines recommend a comprehensive approach. This concurrent validation study developed a School Readiness Index (SRI) with five readiness domains: early learning skills, approach to learning, cognitive skills, socioemotional development, and physical health. Through a cross-sectional comparative design, the school readiness skills of 119 Puerto Rican children (63 males, 56 females) aged 54–65 months were assessed using standardized tests (e.g., Batería IV Woodcock-Muñoz and NIH Toolbox Cognition Battery), parental questionnaires (e.g., Ages and Stages Questionnaire-3), and physical health assessments. Each measure was scored and classified using a binary coding system (0 and 1) based on participant abilities (e.g., 1 for expected performance, 0 if below expectations). A composite SRI score was calculated using 25 indicators. Discriminant validity was assessed by comparing children’s registration status in the special education program (SEP). Sex, household income, and maternal education are key determinants of school readiness. Children registered in the SEP had significantly lower composite scores than those not registered, supporting the SRI’s discriminant validity. The SRI is a reliable tool for identifying Hispanic children from Puerto Rico who may benefit from additional support. Inclusive and multidisciplinary assessment strategies are essential.